Functional tricuspid regurgitation of degenerative mitral valve disease: a crucial determinant of survival. (16th April 2020) - Essayagh, Benjamin; Antoine, Clémence; Benfari, Giovanni; Maalouf, Joseph; Michelena, Hector I; Crestanello, Juan A; Thapa, Prabin; Avierinos, Jean-François; Enriquez-Sarano, Maurice
Abstract: Aims : To assess functional tricuspid regurgitation (FTR) determinants, consequences, and independent impact on outcome in degenerative mitral regurgitation (DMR). Methods and results : All patients diagnosed with isolated DMR 2003–2011, with structurally normal tricuspid leaflets, prospective FTR grading and systolic pulmonary artery pressure (sPAP) estimation by Doppler echocardiography at diagnosis were identified and long-term outcome analysed. The 5083 DMR eligible patients [63 ± 16 years, 47% female, ejection fraction (EF) 63 ± 7%, and sPAP 35 ± 13 mmHg] presented with FTR graded trivial in 45%, mild in 37%, moderate in 15%, and severe in 3%. While pulmonary hypertension (PHTN-sPAP ≥ 50 mmHg) was the most powerful FTR severity determinant, other strong FTR determinants were older age, female sex, lower left ventricle EF, DMR, and particularly atrial fibrillation (AFib) (all P  ≤ 0.002). Functional tricuspid regurgitation moderate/severe was independently linked to more severe clinical presentation, more oedema, lower stroke volume, and impaired renal function ( P  ≤ 0.01). Survival (95% confidence interval) throughout follow-up [70% (69–72%) at 10 years] was strongly associated with FTR severity [82% (80–84%) for trivial, 69% (66–71%) for mild, 51% (47–57%) for moderate, and 26% (19–35%) for severe, P  < 0.0001]. Excess mortality persisted after comprehensive adjustment [adjusted hazard ratio 1.40 (1.18–1.67) for moderate FTR and 2.10 (1.63–2.70) for severe FTR, P  ≤ 0.01]. Excess mortality persisted adjusting for sPAP/right ventricular function ( P  < 0.0001), by matching [adjusted hazard ratios 2.08 (1.50–2.89), P  < 0.0001] and vs. expected survival [risk ratio 1.79 (1.48–2.16), P  < 0.0001]. Within 5-year of diagnosis valve surgery was performed in 73% (70–75%) and 15% (13–17%) of severe and moderate DMR and in only 26% (19–34%) and 6% (4–8%) of severe and moderate FTR. Valvular surgery improved outcome without alleviating completely higher mortality associated with FTR ( P  < 0.0001). Conclusion : In this large DMR cohort, FTR was frequent and causally, not only linked to PHTN but also to other factors, particularly AFib. Higher FTR severity is associated at diagnosis with more severe clinical presentation. Long term, FTR is independently of all confounders, associated with considerably worse mortality. Functional tricuspid regurgitation moderate and even severe is profoundly undertreated. Thus careful assessment, consideration for tricuspid surgery, and testing of new transcatheter therapy is warranted.